1979
DOI: 10.1113/jphysiol.1979.sp012611
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of intramembrane charge in Myxicola giant axons.

Abstract: [15][16][17][18][19][20] mV from the normalized Na inactivation curve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…Similar results have been reported for crayfish giant axons (Swenson, 1980), frog node of Ranvier (Nonner, 1980), and frog skeletal muscle (Campbell, 1983). However, a lack of correlation between charge immobilization and INa inactivation has been reported in squid (Meves and Vogel, 1977) and Myxicola (Bullock and Schauf, 1979) giant axons. In the present report we found that the value of %, measured from the decay of INa during maintained depolarizations, varied by as much as a factor of 3 among patches at the same potential (Table III), and no systematic difference in *h was observed between cell-attached and inside-out patches.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been reported for crayfish giant axons (Swenson, 1980), frog node of Ranvier (Nonner, 1980), and frog skeletal muscle (Campbell, 1983). However, a lack of correlation between charge immobilization and INa inactivation has been reported in squid (Meves and Vogel, 1977) and Myxicola (Bullock and Schauf, 1979) giant axons. In the present report we found that the value of %, measured from the decay of INa during maintained depolarizations, varied by as much as a factor of 3 among patches at the same potential (Table III), and no systematic difference in *h was observed between cell-attached and inside-out patches.…”
Section: Discussionsupporting
confidence: 86%
“…The decline in TOFF with pulse durations that would have produced significantly increasing sodium inactivation has been previously observed in both squid axons (Fig . 2 of Armstrong and Bezanilla, 1977) and node of Ranvier (Nonner et al ., 1978 ;Nonner, 1980), but not in Myxicola axons (Table I of Bullock and Schauf, 1979) . These comparisons seem to indicate that the sodium channel gating processes may be similar in squid and frog axons, at least insofar as can be determined from gating charge movement measurements, but that both may differ from the gating process in Myxicola axons.…”
Section: Comparison With Previous Observationsmentioning
confidence: 95%
“…Independently of whether the inactivation blocking site is a component of the normal gating machinery or not, it is clear that if some fraction of resting channels have this site occupied, by e.g., K, then these channels inherently have inactivation coupled to activation in that a conducting channel is necessary to clear the sites and so permit the inactivation gates to close. The nature of the coupling between activation and inactivation certainly involves more just this effect, however, as immobilization of the gating charge (Armstrong and Bezanilla, 1977;Meves and Vogel, 1977;Neumcke et al, 1976;Nonner et al, 1978;Nonner, 1980;Bullock and Schauf, 1979;Swenson, 1980;Starkus et al, 1981) establishes that the operation of the activation gates is itself dependent on the inactivation state of the channel, and because channels can also inactivate without conducting (Gillespie and Meves, 1980;Bean, 1981;Horn et al, 1981;Aldrich et al, 1983;Horn and Vandenberg, 1984). I thank Drs.…”
Section: A Possible Mechanism For Inactivationmentioning
confidence: 99%